Mathematical statistical analysis of attainment levels of primary left handed students based on pearson's conformity criteria - Kuldoshev, Rustambek; Nigmatova, Mavjuda; Rajabova, Iroda; Raxmonova, Gullola (E3S web of conferences, 2023)
Quantitative changes in improving the effectiveness of teaching writing and developing the skills of elementary school students were summarized in the assessment of teaching effectiveness using Student and Pearson methods. Using the χ ^2 Pearson test, which is often used in statistical research, we introduce the research hypotheses of the second, third and final stages of the control and experimental class participants with the indicators of the first stage. At the end of the experimental work, it was proven that the respondent's knowledge indicators increased by 13.8% on average.